Towards implementing context-aware dynamic text field for web-based data collection. (2016) - Chala, Sisay Adugna; Ansari, Fazel; Fathi, Madjid
Capturing data in web-based system can be done using open-ended and/or close-ended user interface elements. In open-ended format, users can enter anything, whereas in close-ended formats users can choose from predefined options to enter data. While allowing users to freely give response without limiting options, open-ended user interface components pose high pressure on the respondent-side and have higher processing costs. On the other hand, close-ended data capturing components pose pressure on the part of designers of user interfaces to predict the respondents' choices and still limit the options on the user side while they store data that are less challenging to process. This study sets out to contribute to the current research by designing and implementing a context-aware dynamic text field for data collection in web-based occupational information systems.